Dental Pulp Vascular Response to Early Stages of Caries - Aljaž Golež; Ksenija Cankar; Aleksandra Milutinović; Lidija Nemeth; Ana Tenyi (Elsevier, 2024)
Objectives: During caries progression, dental pulp is increasingly pathologically affected. Since the accurate assessment of pulp is of vital importance in clinical decision-making, this study aimed to evaluate pulpal condition in the early stages of caries via laser Doppler (LD) flowmetry and histologic analysis and determine their agreement. Methods: Fourteen patients with severe dental crowding were included. Prior to extractions and orthodontic treatment, dental pulp condition of 52 premolars was evaluated via LD flowmetry. Teeth were assessed for the presence of caries and lesions were graded according to the International Caries Detection and Assessment System (ICDAS). After extractions, teeth were split and histologically stained for endothelial cells with anti-von Willebrand factor and Movat pentachrome for collagen. Volume densities of vessels (Vvasc) and collagen were calculated. Results: There was a significant negative correlation between LD flow and Vvasc of the dental pulp with ICDAS grade. Pulpal LD flow and Vvasc in teeth with the initial lesion were increased, decreasing with progressing stages of caries. A significant positive correlation between the the pulpal LD flow and Vvasc, and a negative correlation of LD flow with collagen fibre density were noted. Conclusions: Caries affects the physiology of the dental pulp, initially with increasing vascularity, and decreasing vascularity at later stges of caries progression. Collagen contents increase with grades of ICDAS. LD flow shows good agreement with the histologic constitution of the dental pulp. Use of clinical measurements of pulpal LD flow could provide a good noninvasive indication of pulpal vascular state and its health.